Reconsidering the case study method in management education - Christopher Orpen (South African Journal of Business Management, 1982)
This paper argues that recent criticisms of the case study method are not well-founded and that, on the contrary, there are good reasons why it should be a major, or even the dominant, mode of instruction at business schools. As a method, case studies possess a number of distinct advantages over lectures/tutorials in helping students acquire those practical skills in diagnosing and solving problems that serve to distinguish effective from ineffective managers. It is the case study method which also serves to distinguish management from other subjects and gives it the coherence it needs to be regarded as a discipline in its own right. It is argued that for these reasons the current swing away from the case study method at many business schools should be reversed.
Keywords: 650